2005
DOI: 10.1103/physreve.72.026131
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized scale-free networks

Abstract: Growth and preferential attachments have been coined as the two fundamental mechanisms responsible for the scale-free feature in complex networks, as characterized by an algebraic degree distribution. There are situations, particularly in biological networks, where growth is absent or not important, yet some of these networks still exhibit the scale-free feature with a small degree exponent. Here we propose two classes of models to account for this phenomenon. We show analytically and numerically that, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 22 publications
1
56
0
1
Order By: Relevance
“…This is the role of the factors of (1 − Π). Such terms are not normally found in the master equations for network rewiring [3,5,6,7,8,9,11]. It is crucial that we do this otherwise we will not have the correct behaviour at the boundaries k = 0 and k = E.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the role of the factors of (1 − Π). Such terms are not normally found in the master equations for network rewiring [3,5,6,7,8,9,11]. It is crucial that we do this otherwise we will not have the correct behaviour at the boundaries k = 0 and k = E.…”
Section: The Modelmentioning
confidence: 99%
“…The classic example of Watts and Strogatz [1] is of this type and such models are often studied in their own right [2,3,4,5,6,7]. Network rewiring is also related to to some multi-Urn models [8,9,10,11] which include what are termed Backgammon or Balls-in-Boxes models [12] used for glasses [13,14], simplicial gravity [15] and wealth distributions [16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mechanisms have been proposed that can produce stable topological metrics in networks of constant size (9)(10)(11)(12). Notably, methods based on percolation theory have significantly contributed to our understanding of how robust the static network structures generated by these assembly mechanisms are to fragmentation under random and targeted attack (8,(13)(14)(15).…”
mentioning
confidence: 99%
“…Previous research showed that the degree exponents from a scale-free network such as the World Wide Web were typically g Ն2 ; however, those from scale-free spatial networks of biological origin have been found to be P(k)ϰ k Ϫ1 (Hermann et al, 2003). Park et al (2005) suggested that two classes of model exhibited the scale-free property with and without growth of the network. According to these authors, the scale-free property of the network might arise through a self-organising mechanism via the natural evolution of links in the network, even without any growth mechanism.…”
Section: ϫGmentioning
confidence: 99%